2016
DOI: 10.1002/2016gl068770
|View full text |Cite
|
Sign up to set email alerts
|

Airborne radar imaging of subaqueous channel evolution in Wax Lake Delta, Louisiana, USA

Abstract: Shallow coastal regions are among the fastest evolving landscapes but are notoriously difficult to measure with high spatiotemporal resolution. Using Uninhabited Aerial Vehicle Synthetic Aperture Radar (UAVSAR) data, we demonstrate that high signal‐to‐noise L band synthetic aperture radar (SAR) can reveal subaqueous channel networks at the distal ends of river deltas. Using 27 UAVSAR images collected between 2009 and 2015 from the Wax Lake Delta in coastal Louisiana, USA, we show that under normal tidal condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 22 publications
(30 reference statements)
2
39
0
Order By: Relevance
“…In total, the subaerially exposed portion of WLD accumulated 6.7 × 10 5 m 3 during the study period. For scale, volumetric change calculated between 2011 [ Shaw and Mohrig , ] and 2015 [ Shaw et al ., ] for the 70.3 km 2 subaqueous front of WLD was 1.9 × 10 6 m 3 . Subaerial deposition was 35% of subaqueous deposition for these partially overlapping 4 year periods.…”
Section: Resultsmentioning
confidence: 99%
“…In total, the subaerially exposed portion of WLD accumulated 6.7 × 10 5 m 3 during the study period. For scale, volumetric change calculated between 2011 [ Shaw and Mohrig , ] and 2015 [ Shaw et al ., ] for the 70.3 km 2 subaqueous front of WLD was 1.9 × 10 6 m 3 . Subaerial deposition was 35% of subaqueous deposition for these partially overlapping 4 year periods.…”
Section: Resultsmentioning
confidence: 99%
“…The apex of this flow expansion is at 29.471°N, 91.487°W (Figure 1b). Distances from the apex to the crest of these three shoals are measured in bathymetric maps collected in June 2010, August 2011, and February 2015 (Shaw, Ayoub, et al, 2016;Shaw & Mohrig, 2014). Flood Table 1 Key Boundary Conditions and Measurements (Bold) From Experimental and Field Data Used in This Experiment discharge to this site has been measured to be about 360 m 3 /s (Hiatt & Passalacqua, 2015;Shaw, Mohrig, et al, 2016).…”
Section: Field Datamentioning
confidence: 99%
“…Our analysis found that streaklines were difficult to measure in Landsat 1 and Landsat 2 imagery, but possible in some cases. Streaklines have also been observed in imagery flown from planes and in SAR imagery (Shaw et al, 2016a). This means that the FD2C method can be used to monitor the decadal change of deltas, ranging from the Wax Lake Delta presented here to other sites such as the West Bay diversion of the main stem Mississippi River where land building and sediment retention are explicit goals (Allison et al, 2017;Andrus and Bentley, 2007;Kolker et al, 20 2012).…”
Section: Each Of the δL Distributions Have Significant Standard Deviamentioning
confidence: 69%
“…However, most deltas are far larger than their sub-aerial portions. For instance, the subaerial area of the Wax Lake Delta in 2015 was 50 25 km 2 (Olliver and Edmonds, 2017) while the subaqueous area was an additional 82 km 2 (Shaw et al, 2016a). The difference arises because the Wax Lake Delta has an extensive delta front deposit that lies below low tide.…”
Section: Introductionmentioning
confidence: 99%